1996
DOI: 10.1016/s0022-5347(01)66131-7
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the Afferent Antireflux Valve Mechanism in the Kock Ileal Reservoir

Abstract: We report an overall complication rate of 10.4% associated with the afferent antireflux nipple valve in the Kock ileal reservoir. Most complications can be treated endoscopically without difficulty on an outpatient basis with the use of local sedation. With these results, and only a 3% incidence of open surgical correction of all afferent nipple problems, we encourage the continued use of the intussuscepted afferent nipple valve whenever continent urinary diversion is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…However, patients with a Kock pouch were significantly more likely to require surgical revision for three main complications, i.e. stenosis, calculi and prolapse of the ileal nipple [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with a Kock pouch were significantly more likely to require surgical revision for three main complications, i.e. stenosis, calculi and prolapse of the ileal nipple [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, this superiority should not be achieved by increasing the risk of upper urinary tract deterioration. Stein et al [10] reported that a low pressure reservoir should be applied with any type of continent uri-Okuno/Coronel/Yanagawa/Takeda/ Kawamura nary diversion in order to maintain upper urinary tract functions. A number of reports have been published concerning reservoir capacity and pressure with regard to the configuration of the upper urinary tract on IVP.…”
Section: Discussionmentioning
confidence: 99%
“…However, this risk appears, to be appreciatively higher after an antireflux technique than after direct anastomosis, irrespective of the anastomosis technique and the segment of bowel used 11,24,25 with a reported stricture rate of 1-4% for the direct anastomosis and of 9.5-20% for the different antireflux techniques described in M A N U S C R I P T…”
Section: Anastomotic Stricture: Refluxing Vs Nonrefluxing Techniquesmentioning
confidence: 99%
“…Dilatation of the upper urinary tract is the major concern in ureteroileal anastomosis 11 and can be caused by strictures of the ureter and reflux 7 .…”
Section: Introductionmentioning
confidence: 99%